2022
DOI: 10.1038/s41598-022-14487-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis to delineate high-quality SNPs for seed micronutrient density in chickpea (Cicer arietinum L.)

Abstract: Chickpea is the most important nutrient-rich grain legume crop in the world. A diverse core set of 147 chickpea genotypes was genotyped with a Axiom(®)50K CicerSNP array and trait phenotyped in two different environments for four seed micronutrients (Zn, Cu, Fe and Mn). The trait data and high-throughput 50K SNP genotypic data were used for the genome-wide association study (GWAS). The study led to the discovery of genes/QTLs for seed Zn, Cu, Fe and Mn, concentrations in chickpea. The analysis of seed micronut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Numerous GWAS have been conducted in chickpea to identify SNPs significantly associated with agronomic traits 48 51 , stress tolerance 52 , 53 , and nutritional traits 20 , 50 , 54 , 55 . However, no GWAS have been reported for fatty acids in chickpea to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous GWAS have been conducted in chickpea to identify SNPs significantly associated with agronomic traits 48 51 , stress tolerance 52 , 53 , and nutritional traits 20 , 50 , 54 , 55 . However, no GWAS have been reported for fatty acids in chickpea to date.…”
Section: Discussionmentioning
confidence: 99%
“…3 a), which follows previous studies in chickpea 67 . However, some studies reported two or three subpopulations in chickpea 20 , 50 , 54 , 55 . These seven subpopulations represent the diverse ancestral background of chickpea.…”
Section: Discussionmentioning
confidence: 99%
“…(2022) reported significant genetic variation in 258 chickpea accessions for various nutritional components: Fe (2.26–7.25 mg 100 g –1 , mean: 4.36), Ca (60.7–176.5 mg 100 g –1 , mean: 108.6), Mg (64.08–134.57 mg 100 g –1 , mean: 100.35), Mn (0.67–3.73 mg 100 g –1 , mean: 1.78), phytic acid (2.07–19.38 mg g –1 , mean: 10.68), and Zn (1.15–4.59 mg 100 g –1 , mean: 2.76. Similarly, Fayaz et al. (2022) reported significant genetic variation in various micronutrients in 147 chickpea genotypes over a two-year evaluation: Zn (1.45–20.49 and 0.936–20.58 mg 100 g –1 , Fe (7.93–19.82 and 10.36–12.72 mg 100 g –1 ), Cu (0.42–18.54 and 0.366–19.03 mg 100 g –1 ), and Mn (0.907–5.43 and 0.48–12.28 mg 100 g –1 ) and Farida Traore et al.…”
Section: Micronutrientsmentioning
confidence: 98%
“…Furthermore, genotyping 92 sequenced desi and kabuli accessions with 24,620 SNPs identified 16 genomic loci/genes contributing to seed Fe and Zn, accounting for a combined 29% PVE ( Upadhyaya et al., 2016a ). Subsequently, a GWAS on a diverse panel of 147 chickpea genotypes phenotyped for two years and genotyped with an “Axiom ® 50K CicerSNP array” identified 35 significant marker-trait associations (MTAs) contributing to grain Zn, Fe, Cu, and Mn, with five MTAs consistently identified in different environments (stable), six explaining more than 15% of the phenotypic variation (major), and three both stable and major MTAs ( Fayaz et al., 2022 ). Likewise, over two years, SNP204 on LG1 and SNP9478 on LG5 showed significant MTAs for Fe content at Sanliurfa, and SNP8254 and SNP8255 on LG4 showed significant MTAs for Fe content at Bornova ( Karaca et al., 2020 ).…”
Section: Genomic Resources For Improving Nutrientsmentioning
confidence: 99%